Oxidative stress induces cell death partially by decreasing both mRNA and protein levels of nicotinamide phosphoribosyltransferase in differentiated PC12 cells - Zhou,Cuiyan; Ying,Weihai (PeerJ, 2021)
Background. Multiple studies have indicated crucial roles of NAD+ deficiency in several neurological diseases and aging. It is critical to discover the mechanisms underlying the NAD+ deficiency. A decreased level of Nicotinamide phosphoribosyltransferase (Nampt)—an important enzyme in the salvage pathway of NAD+ synthesis—has been found under certain pathological conditions, while the mechanisms underlying the Nampt decrease are unclear. The purpose of this study is to test the hypothesis that oxidative stress can produce decreased Nampt, and to investigate the biological effects of Nampt on NAD+ synthesis and cell survival under both basal and oxidative stress conditions. Methods. We used differentiated PC12 cells as a cellular model to investigate the effects of oxidative stress on the levels of Nampt. Multiple assays, including flow cytometry-based cell death assays and NAD+ assays were conducted. Results. First, oxidative stress can decrease the levels of Nampt mRNA and Nampt protein; second, Nampt plays significant roles in NAD+ synthesis under both basal conditions and oxidative stress conditions; third, Nampt plays critical roles in cell survival under both basal conditions and oxidative stress conditions; and fourth, oxidative stress produced decreased NAD+ levels and cell survival partially by decreasing Nampt. Collectively, our study has indicated that oxidative stress is a pathological factor leading to decreased Nampt, which plays important roles in oxidative stress-produced decreases in NAD+ levels and cell survival. Our findings have indicated major roles of Nampt in maintaining NAD+ levels and cell survival under both basal and oxidative stress conditions.
Keywords: Nicotinamide phosphoribosyltransferase; NAD+; Oxidative stress; Cell death; Aging